2021
DOI: 10.1088/1755-1315/725/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ultimate burst pressure and comparison of failure criteria for thermoplastic composite pipes

Abstract: Thermoplastic composite pipes (TCPs) are becoming the ideal substitute for traditional steel pipe due to its superiorities including light weight and corrosive resistance. The cross-section of TCPs consists of an inner liner, a laminate layer, and an outer jacket. The laminate layer is made of multi-plies of helically wound continuous fibre reinforced unidirectional tape. In the present study, a three-dimensional (3D) theoretical model and a 3D finite element model were developed to analyse the stress state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…According to a study by the Plastic Pipe Database Committee (PPDC) of the United States, design and installation errors account for the largest proportion of PVC pipe failure causes, followed by material defects (Figure 2), meaning that inappropriate pipe products with working pressure specifications that do not meet the requirements were selected and installed in the pipe engineering design and construction. In addition, several researchers have found that extreme water pressure caused by water hammers is one of the most common factors affecting PVC pipe bursts [10][11][12][13]. For the ultimate strength analysis, the burst pressure of a pipe is an important parameter in PVC pipeline design and safe operation, which is determined as the internal water pressure resulting in pipe rupture.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by the Plastic Pipe Database Committee (PPDC) of the United States, design and installation errors account for the largest proportion of PVC pipe failure causes, followed by material defects (Figure 2), meaning that inappropriate pipe products with working pressure specifications that do not meet the requirements were selected and installed in the pipe engineering design and construction. In addition, several researchers have found that extreme water pressure caused by water hammers is one of the most common factors affecting PVC pipe bursts [10][11][12][13]. For the ultimate strength analysis, the burst pressure of a pipe is an important parameter in PVC pipeline design and safe operation, which is determined as the internal water pressure resulting in pipe rupture.…”
Section: Introductionmentioning
confidence: 99%